Learning Style Visual Strategies, Optimization of Visual Strategies to Enhance Learning Styles Differences: A Classroom Action Research (CAR) - Saimima, Sarah Margaretha; Tarumingkeng, Rudy C.; Heryanto, Januar; Kusumadjaja, Maya Devi (Jurnal Inovasi Pendidikan MH Thamrin, 2025)
The success of learning is not only determined by the teaching materials and the teacher's ability to convey information, but also depends greatly on how far the strategies used are able to accommodate the diversity of student characteristics, especially learning styles. In reality, students in the classroom have different learning preferences, some understand better through visual stimulation, auditory information, and some through physical movement or direct touch. This study aims to evaluate the effectiveness of visual activity-based learning strategies in accommodating the different learning styles of seventh-grade junior high school students. In the context of the diversity of student learning styles—be they visual, auditory, kinesthetic, or a combination of the three—an adaptive, engaging instructional approach is needed that is able to optimally facilitate individual needs. This study uses a Classroom Action Research (CAR) approach implemented in two cycles, with the application of visual strategies in the form of drawing and coloring activities integrated with mind mapping techniques to respond to the needs of visual, kinesthetic, and auditory or mixed students. The results showed an increase in student learning engagement from 88.6% in the first cycle to 99.33% in the second cycle. Students demonstrated active participation, increased self-confidence, and a stronger understanding of concepts. This strategy also encouraged the creation of an inclusive learning environment that was responsive to diverse learning styles. These findings emphasize the urgency of using visual strategies as a form of learning differentiation in heterogeneous classroom contexts, while enriching pedagogical approaches that holistically integrate students' cognitive, affective, and psychomotor aspects.